Domestication Of Customary Law : Critique of Legal Centralism in Government Regulation Number 5 Of 2025 Concerning Procedures and Criteria for Determining Living Law in Society from the Perspective of Weak Legal Pluralism - I Putu Sastra Wibawa Wibawa (IAHN-TP Palangka Raya, 2026)
This study aims to analyze the position of customary law in the national legal system following the enactment of Government Regulation Number 55 of 2025 Concerning Procedures and Criteria for Determining Living Law in Society. Using John Griffiths' legal pluralism theoretical framework, this study examines whether the regulation grants full autonomy to customary law or strengthens the dominance of state law. The method used is normative juridical with a conceptual approach. The research findings indicate that GR 55/2025 tends to be categorized as weak legal pluralism. This is because recognition of customary law still relies heavily on state-acknowledged validation, where customary norms are only considered valid to the extent they do not conflict with national interests and statutory regulations. This article concludes that despite codification efforts, the relationship between state law and customary law remains hierarchical and unequal.